2003
DOI: 10.4049/jimmunol.171.11.5828
|View full text |Cite
|
Sign up to set email alerts
|

The Duration of Signaling through CD40 Directs Biological Ability of Dendritic Cells to Induce Antitumor Immunity

Abstract: Although it has been demonstrated that the functions of dendritic cells (DCs), including Ag capture, Ag presentation, and migratory activity, change dynamically with their maturation, the most appropriate conditioning of DCs for anticancer immunotherapy is still unclear. The help signal is one of the most potent stimuli for DC maturation and is provided by the interaction of CD40 expressed on DCs with CD40 ligand on CD4+ T cells. To elucidate the appropriate conditioning of DCs for anticancer immunotherapy, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 43 publications
2
30
0
3
Order By: Relevance
“…Either in the initiation phase or in the effector phase, different outcomes could be obtained by providing with CD40 stimulation and the duration of stimulation. Consistent with other report, 15 the usage of iDCs for the priming phase could provide significant advantages in anticancer immunotherapy. In this study, we fully utilized the dual biological characteristics of DCs, that is, iDCs have the highest engulfing function to uptake the tumor apoptotic bodies and iDCs undergoing maturation by stimulating of CD40L in the tumor micro environmental possess the highest migratory activity to be able to effectively activate specific antitumor CTL.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Either in the initiation phase or in the effector phase, different outcomes could be obtained by providing with CD40 stimulation and the duration of stimulation. Consistent with other report, 15 the usage of iDCs for the priming phase could provide significant advantages in anticancer immunotherapy. In this study, we fully utilized the dual biological characteristics of DCs, that is, iDCs have the highest engulfing function to uptake the tumor apoptotic bodies and iDCs undergoing maturation by stimulating of CD40L in the tumor micro environmental possess the highest migratory activity to be able to effectively activate specific antitumor CTL.…”
Section: Discussionsupporting
confidence: 77%
“…However, the most suitable conditioning of DCs for anticancer immunotherapy is not entirely clear. Watanabe et al 15 found that iDCs could provide significant advantages in anticancer immunotherapy rather than mDCs due to their ability to prime T cells in secondary lymphoid organs through immobilized anti-CD40 antibody stimulation model in vitro.…”
mentioning
confidence: 99%
“…5). Recently it was reported that the duration of stimulation through CD40 influences migratory activity in vivo (30). CCR7 expression was increased when DCs were stimulated with anti-CD40 for 3 h, whereas it was decreased when DCs were stimulated with anti-CD40 for 24 h. Because DCs have a chance to interact with T cells in vivo, migratory activity of DCs in vivo could be different from in vitro migratory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings add to the existing knowledge that immobilized antibodies, such as those directed at CD3, 54 CD47, 55 or CD40, 56 display different biological ability on target cells from their soluble counterparts, and establish that ligation of CD22 by immobilized epratuzumab perturbs BCRmediated signals in malignant B cells without the involvement of anti-BCR antibodies. We also uncover, for the first time, a role of immobilized epratuzumab to stabilize F-actin and the potential of soluble epratuzumab to promote the adhesion of B cells to endothelial cells, which may occur in vivo to manifest the various biological activities observed for the immobilized epratuzumab in vitro.…”
Section: Discussionmentioning
confidence: 60%